2007
DOI: 10.1002/eji.200737752
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐chromatin antibodies drive in vivo antigen‐specific activation and somatic hypermutation of rheumatoid factor B cells at extrafollicular sites

Abstract: A dominant type of spontaneous autoreactive B cell activation in murine lupus is the extrafollicular generation of plasmablasts. The factors governing such activation have been difficult to identify due to the stochastic onset and chronic nature of the response. Thus, the ability to induce a similar autoreactive B cell response with a known autoantigen in vivo would be a powerful tool in deciphering how autoimmune responses are initiated. We report here the establishment and characterization of a system to ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
100
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(113 citation statements)
references
References 97 publications
(145 reference statements)
11
100
0
Order By: Relevance
“…We have been using AM14 B-cell receptor (BCR) transgenic (Tg) mice (AM14), specific for self-IgG2a of the "a" allotype [rheumatoid factor (RF) specificity], to study spontaneous and induced RF responses that both use the EF pathway (5,12). AM14 B cells are activated by IgG2a antichromatin in vitro and in vivo in a TLR-dependent fashion (13,14).…”
mentioning
confidence: 99%
“…We have been using AM14 B-cell receptor (BCR) transgenic (Tg) mice (AM14), specific for self-IgG2a of the "a" allotype [rheumatoid factor (RF) specificity], to study spontaneous and induced RF responses that both use the EF pathway (5,12). AM14 B cells are activated by IgG2a antichromatin in vitro and in vivo in a TLR-dependent fashion (13,14).…”
mentioning
confidence: 99%
“…This is particularly relevant to SLE because autoreactive B cells that recognize and internalize DNA activate TLR9 and may also be exposed to excessive CD40-mediated signals and cytokines. Although extrafollicular B cells do not undergo extensive somatic mutation, they may still secrete pathogenic autoantibodies [12,13]. Plasma cells derived from the extrafollicular focus are dependent on BAFF and a proliferationinducing ligand (APRIL) for their immediate survival but they are short-lived, surviving an average of 3-4 days [11,16].…”
mentioning
confidence: 99%
“…It is not clear why, in the same patient, the plasma cells with different specificities differ in their lifespan. One possibility is that TLR9 engagement by DNA preferentially directs DNA-specific B cells to extrafollicular foci [12]. Alternatively, there might be differences in the signals downstream of TLR engagement by DNA versus RNA or in the cytokine microenvironment in which the different specificities arise.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Histological examination demonstrated that these antibody-secreting cells localize at the red pulp/T cell border (Fig. 3 I), a site previously shown to harbor autoreactive antibody-producing cells (Herlands et al, 2007;Nickerson et al, 2013a). We did not observe YFP + Ars/A1 B cell-containing germinal centers in any time point examined (unpublished data).…”
Section: Res Ults Ship-1 Is Required For the Maintenance Of B Cell Anmentioning
confidence: 54%